Integration of Security Architecture and Green Information Technology in the Implementation of Nextcloud in a Data Center - Pambudi, Tio; Herwanto , Patah (Journal Research of Social Science, Economics, and Management, 2025)
As digital infrastructure continues to expand, institutions are increasingly seeking data storage solutions that are both secure and energy efficient. This study presents the implementation of Nextcloud in a controlled data center environment, combining cybersecurity principles with Green IT strategies. The system was built on Linux Mint using Snap, and configured for public access via dynamic IP and custom port forwarding. Security was assessed through port scanning, firewall configuration, and evaluation using the KAMI Index. Energy consumption was measured with a digital wattmeter and monitored in real time using system tools. The results showed a 22 point improvement in security score and a 26.7% reduction in power usage. These findings suggest that integrating Zero Trust Architecture with energy saving practices can significantly enhance system reliability and sustainability. The proposed model offers a practical reference for institutions aiming to deploy secure, self-hosted cloud services with minimal environmental impact.